Estratégias de marketing para comercialização de produtos agroindustriais: o caso da Escola Agrotécnica Federal de Alegrete - Almeida, Darlon Alves de (2005)
The research develops some understanding to assess and propose some strategies of marketing for the commerce of agro-industrial products manufactured at the Federal Agro-technical School in Alegrete (FASA), and the influence of the variants of marketing-mix in the customer s decision of purchases. The union of this organized marketing is understood as having four primary elements: product, price, market, and sales promotion which combine themselves to achieve the client s satisfaction in the aimed segment and, in this case, those who buy the products from FASA. It also intends to analyze the satisfaction towards the products FASA. Considering those variants mentioned above it is possible to identify the difficulties found by FASA in order to sell their products, to find out relevant technical and behavioral details and to create actions and strategies of the marketing-mix for the commerce of products according to what is proposed. A case study as strategy of research has been used. As a research instrument, a questionnaire and a semi-structured interview have been used. In the initial phase, exploratory studies have been used and, to complement, a method of descriptive study as the main methodological resource has been used. The sample has been composed by 322 interviewees through the analysis of the customers of FASA products in the years 2004 and 2005. The results show that the variety of these products is good for most interviewees. When asked about the price, 69% of the interviewees told it is moderate comparing to other competitors and other 22% say the price is low. When asked about how easy it is to find the products most people answered by saying that it is regular or poor. About the sales promotions, 40% consider them regular, 20% poor and, 9% too poor, adding up to 69%. However, the quality of FASA products is recognized, 85% state that the products have excellent or good quality comparing to other competitors. According to this analysis, it is concluded that FASA products have good acceptance in the marketing, their prices are moderate comparing to the ones of the competitors and, it is necessary to use strategies related to sales promotions and analyze the variant market as a decisive factor for the low index of loyalty of FASA products because of the difficulty in finding the products.